Compiler techniques to improve indirect branch prediction - McCandless, Jason Marshall (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2012)
Computers employ a class of branches called indirect branches to realize various programming language features. Multiway branching (switch statements), virtual function dispatch and function calls are all realized through the use of indirect branch instructions. One of the most important uses of multiway branching is the implementation of virtual machine interpreters, which are commonly used to execute programs written in high-level languages with dynamic features.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin.